Exploring Motivational Factors for Muslims' Cash Waqf Participation: A Case Analysis from Selangor,Malaysia - Mohamad Isa Abd Jalil; Ahmad Aizuddin Hamzah; Imran Mehboob Shaikh; Md Hafizi Ahsan; Joehan Joehari William (Usim Press, 2024)
Journal of Muamalat and Islamic Finance Research (JMIFR) Volume 20 No.2 Page (1-18)